Incomplete Excision Rate for Lentigo Maligna and Associated Risk Factors - Maja Modin; Helena Svensson; Ylva Bergsten Wanders; Noora Neittanmäki; Jan Siarov; John Paoli (Medical Journals Sweden, 2024)
Standard treatment for lentigo maligna (LM) is surgical excision, yet insights into the frequency of and risk factors for incomplete excisions remain limited. The primary objectives were to assess the incomplete excision rate (IER) in primary LM and to explore potential risk factors for incomplete excisions. A retrospective analysis was conducted encompassing consecutive histopathologically confirmed LMs from 2014-2020. Descriptive statistics were used for LM characteristics and IER, while uni- and multivariate analyses were used for calculating risk factors. The study included 395 LMs with an IER of 16.7% (n = 66). Risk factors for higher incomplete excision rates included: head and neck lesions (p = 0.0014), clinical excision margins < 5 mm (p = 0.040), and utilization of preoperative partial biopsies (p = 0.023). Plastic surgeons had higher IERs than dermatologists (p = 0.036). Lesion diameter (p = 0.20) and surgeon experience (p = 0.20) showed no associations with incomplete excisions, yet LMs with a diameter ≥ 20 mm exhibited higher incomplete excision rates (23.2%) compared witho those < 10 mm (12.9%). LMs should be excised with at least 5-mm clinical margins, especially in the head and neck area. LMs ≥ 20 mm may be more surgically challenging. High-er incomplete excision rates associated with the use of preoperative biopsies and/or plastic surgeons may reflect challenging anatomical locations, larger lesion diameter, and/or ill-defined borders.